Prevalence, seasonal variation, and antibiotic resistance pattern of enteric bacterial pathogens among hospitalized diarrheic children in suburban regions of central Kenya. Issue 1 (December 2016) - Shah, Mohammad; Kathiiko, Cyrus; Wada, Akihiro; Odoyo, Erick; Bundi, Martin; Miringu, Gabriel; Guyo, Sora; Karama, Mohamed; Ichinose, Yoshio
Abstract Background The epidemiology of enteric pathogens has not been well studied in Kenya because of wide disparities in health status across the country. Therefore, the present study describes the prevalence of enteropathogenic bacteria, their seasonal variation, and antibiotic resistance profiles among hospitalized diarrheic children in a suburban region of central Kenya. Methods Fecal samples were collected between July 2009 and December 2013 from a total of 1410 children younger than 5 years, hospitalized with acute diarrhea in Kiambu County Hospital, Kenya. Conventional culture, biochemical, and molecular methods were conducted to identify causative bacterial pathogens and their virulence factors. Antimicrobial susceptibility tests were performed using E-test strips and VITEK-2 advanced expert system (AES) to evaluate the drug-resistance pattern of the isolates. Results Of the 1410 isolates, bacterial infections were identified in 474 cases. DiarrheagenicEscherichia coli (DEC) was the most frequently isolated pathogen (86.5%). Other pathogens such asAeromonas (5.5%), Shigella (4%), Salmonella (3.4%), Providencia (3.2%), Vibrio spp. (1.1%), Yersinia enterocolitica (1.1%), andPlesiomonas shigelloides (0.2%) were also identified. Mixed bacterial infection was observed among 11.1% of the cases. The highest infection rate was found during the dry season (59.3%, p  = 0.04). Most of the DEC was found to be multidrug resistant to trimethoprim/sulfamethoxazole 97.6%, amoxicillin 97.6%, erythromycin 96.9%, ampicillin 96.6%, and streptomycin 89%. Conclusions This study suggests that DEC is the leading diarrhea-causing bacterial pathogen circulating in central Kenya, and seasonality has a significant effect on its transmission. Proper antibiotic prescription and susceptibility testing is important to guide appropriate antimicrobial therapy.